THE ROLE OF BUJANG DARA RIAU PROVINCE - Akbar, Faizal; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The study aimed to determine Bujang Dara role and activities Riau Province consideration of the author in using this method of qualitative methods are able to explain the phenomena throuht the collection of data obtained throught interviews. Any data rhat can be processed and clearly defined using a languange that is easily understood. This method does not use the sample population, becauseif the data collected has been profound and explain the phenomenon under study, it is not necessary to find other sampling. This study used a descriptive approach, where this research provides a detailed overview the Role of Bujang Dara Riau Province. While data collection techniques in this research using techniques of observation, interviews and documentation.Based on the research taht has been done, Bujang Dara Has promotion and activities tourism in Riau Province. Promotion is done to help the development of tourism. Promotion of a tourist detination it self indispensable by areas that have potential. Keywords: The Role of Bujang Dara Riau Province